2017
DOI: 10.1140/epjc/s10052-017-5141-x
|View full text |Cite
|
Sign up to set email alerts
|

Accretion onto a noncommutative geometry inspired black hole

Abstract: The spherically symmetric accretion onto a noncommutative (NC) inspired Schwarzschild black hole is treated for a polytropic fluid. The critical accretion rateṀ, sonic speed a s and other flow parameters are generalized for the NC inspired static black hole and compared with the results obtained for the standard Schwarzschild black holes. Also explicit expressions for gas compression ratios and temperature profiles below the accretion radius and at the event horizon are derived. This analysis is a generalizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…In string theory the scalar wave scattering by spherically symmetric d-dimensional black holes has also been analyzed [35]. In [36,37] the authors considering a noncommutative Schwarzschild black hole have explored the effect of the noncommutativity on the matter accretion rate.…”
Section: Introductionmentioning
confidence: 99%
“…In string theory the scalar wave scattering by spherically symmetric d-dimensional black holes has also been analyzed [35]. In [36,37] the authors considering a noncommutative Schwarzschild black hole have explored the effect of the noncommutativity on the matter accretion rate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various properties of NC gravity have been the focus of studies by several authors. These studies include, for example, charged solution of the NCi BH and polytropic fluid matter accretion onto the NCi BH [14,15], Chandrasekhar mass-limit for white dwarfs in the frame of NC gravity [16], rotating NCi BH solution and NCi BH solution in 4D Einstein Gauss Bonnet gravity [17,18], the effects of NC parameter on gravitational measurements such as redshift, deflection, and time delay of light [19], the quasinormal modes of massless scalar field perturbation in NC gravity [20], gravitational lensing and shadow of the NCi BHs [21,22], and quantum tunnel effects of NCi Schwarzschild BHs [23].…”
Section: Introductionmentioning
confidence: 99%
“…A popular way of proposing NC is by defining x i , x j = iη and p i , p j = iθ with η and θ being the NC parameters. It was shown that in the presence of NC, the spacetime metric alters [37], causing the event horizon to shift and the singularity at the centre of a black hole to vanish, which is replaced by a regular de-Sitter core [38][39][40]. It further alters some other properties associated with black holes, such as the stability of Cauchy horizon [41], mini black hole formation with the central singularity replaced by a self-gravitating droplet [42], the Hawking temperature [43].…”
Section: Introductionmentioning
confidence: 99%